Mandatory Audit Rotation Policies and Auditor Independence Implications (gjstudies, 2022)
This research investigates the complex and often paradoxical implications ofmandatory audit rotation (MAR) policies on auditor independence, moving beyondthe conventional economic and regulatory frameworks that have dominated the discourse. While existing literature primarily debates MAR’s efficacy in preventing auditor familiarity and economic dependence on clients, this study introduces a novel,multi-dimensional analytical model that integrates behavioral psychology, institutional theory, and network analysis to deconstruct the independence construct. Weargue that independence is not a binary state but a dynamic continuum influencedby cognitive biases, relational embeddedness, and the institutional logics of auditfirms. Our methodology employs a longitudinal, mixed-methods design, analyzingarchival data from jurisdictions with and without MAR over a 15-year period, combined with in-depth interviews and cognitive mapping exercises with audit partners.The findings reveal a counterintuitive ’compliance paradox’: in rigid MAR regimes,formal independence is enhanced, but substantive, judgment-based independencecan be compromised due to compressed learning curves and intensified commercial pressures during the initial engagement years. Conversely, the study identifiesa ’relational residue’ effect, where auditor-client knowledge networks persist beyond formal rotation, challenging the assumption of a clean slate. Furthermore, wedemonstrate that the effectiveness of MAR is heavily contingent on the underlyinginstitutional environment, including litigation regimes and corporate governancequality. The paper concludes by proposing a tiered, risk-based rotation frameworkas a superior alternative to one-size-fits-all mandates, emphasizing the calibrationof rotation triggers to specific client risk factors rather than arbitrary time periods.1Published: 2022-06-28This research contributes original theoretical insights by reconceptualizing auditorindependence as a systemic property and offers pragmatic, evidence-based policyalternatives